Utopia, Heterotopia, and Mediatopia: Rethinking Foucault and Performativity in Krisna Murti’s Video Artworks - Allo, Katherina; Piliang, Yasraf A. (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2010)
As the epoch of space confronts us with its multiplicity of networks, a new architectonics of space has begun to raise its own construction. Foucault’s terminology of utopia and heterotopia has covered the delineation of the other spaces, spaces which invert, mirror, suspend, and neutralize the real spaces of society. With the propagation of moving images into the space of our daily life, every space at any given moment can turn into an image of utopia as well as a construction of heterotopia. As Foucault says, now is the epoch of space, now is the time to re-value and re-define the contemporary space we live in.